Comparative study of post-transplant outcomes in hepatocellular carcinoma patients treated with chemoembolization or radioembolization. Issue 93 (August 2017) - Gabr, Ahmed; Abouchaleh, Nadine; Ali, Rehan; Vouche, Michael; Atassi, Rohi; Memon, Khairuddin; Asadi, Ali Al; Baker, Talia; Caicedo, Juan Carlos; Desai, Kush; Fryer, Jonathan; Hickey, Ryan; et al.
Abstract: Purpose: To analyze long-term outcomes in patients bridged/downstaged to orthotopic liver transplantation (OLT) by transarterial chemoembolization (TACE) or yttrium-90 radioembolization (Y90) for hepatocellular carcinoma (HCC). Methods: 172 HCC patients who underwent OLT after being treated with transarterial liver-directed therapies (LDTs) (Y90: 93; TACE: 79) were identified. Pre-LDT and pre-OLT clinical/imaging/laboratory characteristics including United Network for Organ Sharing (UNOS) staging and alpha-fetoprotein values (AFP) were tabulated. Post-OLT HCC recurrence was assessed by imaging follow-up per standard of care. Recurrence-free (RFS) and overall survival (OS) were calculated. Uni/multivariate and sub-stratification analyses were performed. Results: Time-to-OLT was longer in the Y90 group (Y90: 6.5 months; TACE: 4.8 months; p = 0.02). With a median post-OLT follow-up of 26.1 months (IQR: 11.1–49.7), tumor recurrence was found in 6/79 (8%) TACE and 8/93 (9%) Y90 patients. Time-to-recurrence was 26.6 (CI: 7.0–49.5) and 15.9 months (CI: 7.8–46.8) for TACE and Y90, respectively ( p = 0.48). RFS (Y90: 79 months; TACE: 77 months; p = 0.84) and OS (Y90: 57% alive at 100 months; TACE: 84.2 months; p = 0.57) were similar. 54/155 patients (Y90: 29; TACE: 25) were downstaged to UNOS T2 or less. RFS hazard ratios for patients downstaged to ≤T2 versus those that were not were 0.6 (CI: 0.33–1.1) and 1.7 (CI: 0.9–3.1) respectively ( p = 0.13). 17/155 patients (Y90: 8; TACE: 9) that were >T2 were downstaged to UNOS T2 or less (within transplant criteria). Distribution (unilobar/bilobar), AFP, and pre-transplant UNOS stage affected RFS on univariate analyses. Conclusion: Despite longer time-to-OLT for Y90 patients, post-OLT outcomes were similar between patients bridged or downstaged by TACE or Y90. A trend towards improved RFS for downstaged patients was identified.